Quality of reporting of clinical non-inferiority and equivalence randomised trials - update and extension - Schiller, Petra; Niestroj, Michael; Kieser, Meinhard (Trials, 2012)
Background: Non-inferiority and equivalence trials require tailored methodology and therefore adequate conduct and reporting is an ambitious task. The aim of our review was to assess whether the criteria recommended by the CONSORT extension were followed. Methods. We searched the Medline database and the Cochrane Central Register for reports of randomised non-inferiority and equivalence trials published in English language. We excluded reports on bioequivalence studies, reports targeting on other than the main results of a trial, and articles of which the full-text version was not available. In total, we identified 209 reports (167 non-inferiority, 42 equivalence trials) and assessed the reporting and methodological quality using abstracted items of the CONSORT extension. Results. Half of the articles did not report on the method of randomisation and only a third of the trials were reported to use blinding. The non-inferiority or equivalence margin was defined in most reports (94%), but was justified only for a quarter of the trials. Sample size calculation was reported for a proportion of 90%, but the margin was taken into account in only 78% of the trials reported. Both intention-to-treat and per-protocol analysis were presented in less than half of the reports. When reporting the results, a confidence interval was given for 85% trials. A proportion of 21% of the reports presented a conclusion that was wrong or incomprehensible. Overall, we found a substantial lack of quality in reporting and conduct. The need to improve also applied to aspects generally recommended for randomised trials. The quality was partly better in high-impact journals as compared to others. Conclusions. There are still important deficiencies in the reporting on the methodological approach as well as on results and interpretation even in high-impact journals. It seems to take more than guidelines to improve conduct and reporting of non-inferiority and equivalence trials.